2022
DOI: 10.1097/01.naj.0000805644.85184.d2
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Nurses' Experiences of Caring for Patients and Families During the COVID-19 Pandemic: Communication Challenges

Abstract: Objective: The purpose of this study was to gain a better understanding of the perceptions and experiences of nurses caring for patients and families under the COVID-19 pandemic's socially restrictive practices and policies. Background: The COVID-19 global pandemic has affected the delivery of health care to patients and their families, with many aspects altered because of the need for social distancing, social isolation, and visitation restriction poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…In these situations, the participants did all they could to use electronic devices (e.g., tablets and cell phones) to enable families to connect and communicate as their loved ones were dying. The nurses found this process to be emotionally draining and inconsistent with the standards of care, findings also reported in other studies (Danielis et al, 2021;De Leo et al, 2021;Pariseault et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…In these situations, the participants did all they could to use electronic devices (e.g., tablets and cell phones) to enable families to connect and communicate as their loved ones were dying. The nurses found this process to be emotionally draining and inconsistent with the standards of care, findings also reported in other studies (Danielis et al, 2021;De Leo et al, 2021;Pariseault et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…Pariseault, Copel and McKay investigated the perceptions and experiences of hospital-based registered nurses caring for patients and their families during the recent pandemic. 1 Several prominent themes were communication challenges and barriers, prioritization of time and resources, and incorporation of timely and regularly scheduled virtual group communication (eg, rounds) between the patient/family/and healthcare team. Nurses working in stroke centers and other settings have come up with creative solutions to help minimize the use of scarce personal protective gear (eg, 3D printers), maintaining open lines of communication with staff and leadership, providing remote family poststroke education, and continuing effective staff collaboration (eg, Adapted Stroke Unit Model) while following COVID-19 guidelines.…”
Section: Acute Carementioning
confidence: 99%
“…Communication challenges have also been identified (Diaz-Agea et al, 2022;Ferrari et al, 2021;Moretti et al, 2021;Pariseault et al, 2022). Nurses reported that PPE and physical distancing made it more difficult to create relational interactions and communication with patients.…”
Section: Introductionmentioning
confidence: 99%
“…For example, relational care, such as talking and listening or non‐verbal communication, was found to be among the fundamental nursing care tasks most often missed for patients with Covid‐19 (Sugg et al, 2021). Communication challenges have also been identified (Diaz‐Agea et al, 2022; Ferrari et al, 2021; Moretti et al, 2021; Pariseault et al, 2022). Nurses reported that PPE and physical distancing made it more difficult to create relational interactions and communication with patients.…”
Section: Introductionmentioning
confidence: 99%